Validation of a method for the determination of sterols and triterpenes in the aerial part of Justicia anselliana (Nees) T. Anders by capillary gas chromatography - KPOVIESSI DOSSOU, SIKA SALOME; Gbaguidi, A. Fernand; Gbénou, Joachim; Accrombessi, Georges; MOUDACHIROU, Mansourou; Rozet, Eric; Hubert, Philippe; QUETIN-LECLERCQ, Joëlle (My University, 2008)
An accurate and sensitive method, combining soxhlet extraction, solid phase-extraction and capillary gas chromatography is described for the quantitative determination of one triterpene (lupeol) and three sterols (stigmasterol, campesterol and -sitosterol) and the detection of another triterpene (-amyrin) from the aerial part of Justicia anselliana. This is the firstmethod allowing the quantification of sterols and triterpenes in this plant. It has been fully validated in order to be able to compare the sterol and triterpene composition of different samples of J. anselliana and therefore help to explain the allelopathic activity due to these compounds. This method showed that the aerial part of J. anselliana contained (292±2) mg/kg of lupeol, (206±1) mg/kg of stigmasterol, (266±2) mg/kg of campesterol and (184±9) mg/kg of - sitosterol.
Keywords: Capillary gas chromatography; Quantification; Sterols; Triterpenes; Justicia anselliana; Acanthaceae